OPTIMALISASI KEPEMILIKAN SAHAM PERUSAHAAN OLEH SERIKAT PEKERJA UNTUK MENINGKATKAN KESEJAHTERAAN PEKERJA DI PT. FISCOUS SOUTH PACIFIC - - Dr. Gunarto, SH, MHum (Majalah Ilmiah Sultan Agung, 2011)
Research on the optimization of company stock ownership by unions backed by the implementation of industrial relations between employers and workers do not realize the welfare of workers. Construction labor laws by providing wage workers are single and minimum wage provisions of Regency / City have made a minimum wage of workers in Indonesia. The research problems are three: First, what are the factors that inhibit the ownership shares of the company by the union? Second, what steps should be taken to improve oversight Â stock ownership by the community against the company by the union? Third, the model of share ownership by unions how to improve the welfare of workers?. The research method used is a qualitative research method kualitatif with normative juridical approach and study of law as the law in action, which is the study of social sciences that are nonÂ doctrinal and empirical. Research results, first the factors that hinder the implementation of share ownership by unions is a normative juridical (concerning the statutory rulemakingÂ invitation), enforcement (the employers and the government's role), juridical and sociological factors (related to economic considerations as well as culture business legal occupant of the rule) that the employer always wants to benefit as much as possible. Second, a variety of legislation mandates the participation in ownership of company shares by trade unions, but there are several factors that hinder the participation of these communities, namely: lack of institutional opening of business, government and law enforcement in providing information about a case of industrial relations. Third, a model program of share ownership by workers through the ESOP is one policy that can be taken by management and workers in Indonesia. Through the ESOP program is an effort to save the company from the possibility of bankruptcy can be avoided.Keywords: Ownership of shares, trade unions, workers' welfare